Research development of STEM faculty as part of a disciplinary professional development program - Hass, Christopher A. F. (Kansas State University, 2023)
Over the past 50 years physics education research (PER) has grown into a thriving sub-discipline of physics. PER grew out of a desire to approach education research and development from a disciplinary perspective, operating under the assumption that good physics education is deeply rooted in the disciplinary knowledge and practices of physicists. As a result of its disciplinary focus, many physics education researchers have informal education research or practice focused backgrounds, in addition to formal backgrounds in traditional physics sub-disciplines such as nuclear physics, AMO physics, condensed matter physics, etc. While there are institutions that offer graduate programs in PER, there are still many new and emerging PER researchers who do not have backgrounds in education research. In an effort to welcome these people to the field, and provide them some formal training in education research practices the professional development for emerging education researchers (PEER) program was born. Over the years, this program has expanded to include researchers from other STEM disciplines as well, making it one of a few programs in STEM available for discipline based education research (DBER) professional development. In this dissertation I will discuss the needs of emerging discipline based education researchers (EDBERs), and how we can better support them in their growth. I will approach this problem through the lens of the PEER program. I will present findings based on iterative thematic analysis of interviews with EDBERs (many of whom were PEER participants). The results of these thematic analyses will be presented across three different projects. The first project focuses on how the community can come together to support EDBERs, and how community connections and support can be built into professional development programs (using PEER as an example). This project covers a thematic analysis that turned up three roles which our EDBERs depend upon community members to fill in order to support their growth and engagement in education research. I begin by interpreting these roles through the lens of behaviour and decision making, in order to explain how these roles fit into a professional development program. Afterwards, I go on to explain the next iteration of the thematic analysis which focused on how EDBERs develop a sense of belonging within the education research community. I tie their sense of belonging back to the roles that community members play in their development as education researchers. Having discussed how EDBERs are linked to the education research community, I move on to their access to the community. In the second project I examine themes around isolation, fear, and stigmatization that emerge in interviews with EDBERs. Here I characterize communities as networks of people, and use Barzilai-Nahon’s theory of network gatekeeping to examine EDBERs access to the education research community, and how the community controls that access. I propose moving explicitly and thoughtfully towards a culture of groundskeeping to help mitigate the negative impacts of gatekeeping on EDBERs. Finally I will examine themes that emerged around the difficulty of engaging with theory in education research. Many faculty EDBERs lack a background in education research, and struggle with theory in interesting ways. In this project I first elaborate on how their struggle with theory manifests in my data. I then go on present case studies of EDBERs thinking explicitly about what theory is in research. In these case studies I present an example of an EDBER sensemaking about theory, a counter example of someone who already has strong but incomplete ideas about theory, and finally an example of an experienced education researcher’s reasoning about theory within education research. These three projects come together to demonstrate the challenges faced by EDBERS, and the support they need from established education researchers in order to thrive. I examine their needs across issues of community support, community access, and understanding of community knowledge in order to provide a multifaceted picture of challenges faced by professionals engaging with a new (to them) field.
Keywords: Professional development; Physics; Education